Mola mola Nyegaard et al. 2018 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Mola mola (Linnaeus, 1758). Mola or Ocean Sunfish. Confirmed to 2.7 m (8.9 ft) TL (Tierney Thys, pers. comm. to M.L.); possibly to 4 m (13.1 ft) TL (Miller and Lea 1972). Circumglobal; western Pacific Ocean north to Japan (Hatooka in Nakabo 2002), and southern Kuril Islands (Parin 2003; Gulf of Alaska (Mecklenburg et al. 2002) to Las Cruces (33°29’S), central Chile (Brito 2003), including Gulf of California (Scott in Fischer et al. 1995), and Islas Galápagos (Grove and Lavenberg 1997). Depth: surface to 844 m (2,768 ft) (min.: Clemens and Wilby 1946; max.: Potter and Howell 2011). Deepest known occurrence off eastern Pacific coast is 556 m (1,824 ft) (Thys et al. 2015). We note that the NWFSC-FRAM database contains a number of records of fish ostensibly caught by bottom trawls at depths deeper than 844 m (e.g., 942 m, 3,090 ft, 954 m, 3,129 ft, 1095 m, 3,592 ft, and 1,184 m, 3,884 ft). However, it is likely that all of these represent catches made in the water column during net deployment or retrieval. ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 226, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...